A three-step approach to assess efficacy of alternative chemical treatments to preserve fresh fruit juices: Application to pineapple (Ananas comosus 'Queen Victoria'). (1st February 2022) - Leneveu-Jenvrin, Charlène; Aboudia, Aouatif; Assemat, Sophie; Remize, Fabienne
Abstract: Fresh pineapple juice exhibits a shelflife of a few days limited by the development of yeasts and molds. An approach was implemented to assess the efficacy of treatments of juice, based on three successive steps. The first step was to validate the use of a microbial cocktail which leads to juice spoilage. In a second step, the efficacy of treatments was assessed on the growth of fungi in two conditions. The treatment chosen was the addition of Thymus leptobotrys (Tl) and Thymus maroccanus (Tm) essential oils (EO). These extracts were mainly composed of the monoterpene carvacrol, and inhibited fungal growth in culture medium. The addition of EO to pasteurized juice inoculated with a fungal cocktail limited fungal population below 4.6 log CFU/mL during 14 days. The low pH of pineapple juice probably strengthened the effect of antifungal compounds acting on proton gradient across plasma membrane. Lastly, the efficacy of the treatments was assessed in fresh pineapple juice harboring its natural microbial population. The extracts TlEO at 0.25‰ or TmEO at 0.05‰ limited fungal growth below 5 log CFU/mL during 14 days. Thyme scent was detected after EO addition but the characteristic descriptors of pineapple and sugary were maintained. Highlights: Spoilage of fresh pineapple juice by a defined fungal cocktail was demonstrated. Pure thymol at 0.25‰ completely inhibited fungal growth. Fungal inhibition caused by thyme essential oils (EO) was showed in vitro and in pasteurized juice. In fresh juice, EO at 0.05‰ limited fungal population below 5 log CFU/mL during 14 days. The approach can be applied to any alternative treatment.